Effect of Oral Re-esterified Omega-3 Nutritional Supplementation on Dry Eyes. Issue 9 (September 2016) - Epitropoulos, Alice T.; Donnenfeld, Eric D.; Shah, Zubin A.; Holland, Edward J.; Gross, Michael; Faulkner, William J.; Matossian, Cynthia; Lane, Stephen S.; Toyos, Melissa; Bucci, Frank A.; Perry, Henry D.
Abstract : Purpose: To assess the effect of oral re-esterified omega-3 fatty acids on tear osmolarity, matrix metalloproteinase-9 (MMP-9), tear break-up time (TBUT), Ocular Surface Disease Index (OSDI), fluorescein corneal staining, Schirmer score, meibomian gland dysfunction (MGD) stage and omega-3 index in subjects with dry eyes and confirmed MGD. Methods: This was a multicenter, prospective, interventional, placebo-controlled, double-masked study. Subjects were randomized to receive 4 softgels containing a total of 1680 mg of eicosapentaenoic acid/560 mg of docosahexaenoic acid or a control of 3136 mg of linoleic acid, daily for 12 weeks. Subjects were measured at baseline, week 6, and week 12 for tear osmolarity, TBUT, OSDI, fluorescein corneal staining, and Schirmer test with anesthesia. MMP-9 testing and omega-3 index were done at baseline and at 12 weeks. Results: One hundred five subjects completed the study. They were randomized to omega-3 (n = 54) and control group (n = 51). Statistically significant reduction in tear osmolarity was observed in the omega-3 group versus control group at week 6 (−16.8 ± 2.6 vs. −9.0 ± 2.7 mOsm/L, P = 0.042) and week 12 (−19.4 ± 2.7 vs. −8.3 ± 2.8 mOsm/L, P = 0.004). At 12 weeks, a statistically significant increase in omega-3 index levels ( P < 0.001) and TBUT (3.5 ± 0.5 s vs. 1.2 ± 0.5 s, P = 0.002) was also observed. Omega-3 group experienced a significant reduction in MMP-9 positivity versus control group (67.9% vs. 35.0%, P = 0.024) and OSDI scores decreased significantly in omega-3 (−17.0 ± 2.6) versus control group (−5.0 ± 2.7, P = 0.002). Conclusions: Oral consumption of re-esterified omega-3 fatty acids is associated with statistically significant improvement in tear osmolarity, omega-3 index levels, TBUT, MMP-9, and OSDI symptom scores.